Effects of drought stress and Morchella inoculation on the physicochemical properties, enzymatic activities, and bacterial community of Poa pratensis L. rhizosphere soil - Wei Yin; Le Wang; Qian Han Shang; Yi Xin Li; Wei Sa; Quan Min Dong; Jian Liang (PeerJ)
Background Soil microorganisms are crucial for plant growth, and both plants and their associated rhizosphere microbes are impacted by changes in soil moisture. Inoculation with beneficial fungi can improve bacterial community structure and soil parameters. Aim Under drought stress conditions, the effects of inoculation with Morchella on the physicochemical properties, enzyme activity, and bacterial community structure of the rhizosphere soil of Poa pratensis were studied. Methods High-throughput sequencing was employed to study rhizosphere soil bacterial communities in both Morchella-inoculated and uninoculated Poa pratensis rhizosphere soil subjected to moderate (50% soil moisture) and severe (30% soil moisture) drought stress, as well as under normal water conditions (70% soil moisture). Results Morchella inoculation significantly increased the alkaline nitrogen (AN) and available phosphorus (AP) contents, protease activity (PA), and alkaline phosphatase activity (APA) of Poa pratensis rhizosphere soil. Both Morchella inoculation and drought stress significantly altered the abundance and diversity of the P. pratensis rhizosphere community. The Chao1, Shannon, and Pielou diversity indices decreased with increasing drought stress. The effect of Morchella inoculation was improved under moderate drought stress and unstressed conditions. In addition, Morchella inoculation may help to stabilize the rhizosphere bacterial community under various levels of soil moisture.